RF positioning fundamentals, applications, and tools - Campos, Rafael Saraiva; Lovisolo, Lisandro (NSS technology and applications series, 2015)
This new resource presents a comprehensive view of radio-frequency (RF) positioning. The book is organized to allow readers to progress at a fast pace, from the fundamentals of RF positioning, to the use of advanced tools such as artificial intelligence algorithms and application development environments